2004
DOI: 10.1021/bi049489p
|View full text |Cite
|
Sign up to set email alerts
|

4-Oxalocrotonate Tautomerase, Its Homologue YwhB, and Active Vinylpyruvate Hydratase:  Synthesis and Evaluation of 2-Fluoro Substrate Analogues

Abstract: A series of 2-fluoro-4-alkene and 2-fluoro-4-alkyne substrate analogues were synthesized and examined as potential inhibitors of three enzymes: 4-oxalocrotonate tautomerase (4-OT) and vinylpyruvate hydratase (VPH) from the catechol meta-fission pathway and a closely related 4-OT homologue found in Bacillus subtilis designated YwhB. All of the compounds were potent competitive inhibitors of 4-OT with the monocarboxylated 2E-fluoro-2,4-pentadienoate and the dicarboxylated 2E-fluoro-2-en-4-ynoate being the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Various groups have proposed that the water would be activated by the metal ion. 4,5,[10][11][12] The strongest support for this mechanism comes from the crystallographic analysis of OHED hydratase carried out by Izumi et al 12 Based on this analysis, the mechanism shown in Figure 3 was formulated. The authors suggested that the metal ion (Mg 2+ ) is coordinated by the C-2 carbonyl group and the C-1 carboxylate group (of 20) based on modeling the substrate into the crystal structure of the enzyme-oxalate complex.…”
Section: Discussionmentioning
confidence: 99%
“…Various groups have proposed that the water would be activated by the metal ion. 4,5,[10][11][12] The strongest support for this mechanism comes from the crystallographic analysis of OHED hydratase carried out by Izumi et al 12 Based on this analysis, the mechanism shown in Figure 3 was formulated. The authors suggested that the metal ion (Mg 2+ ) is coordinated by the C-2 carbonyl group and the C-1 carboxylate group (of 20) based on modeling the substrate into the crystal structure of the enzyme-oxalate complex.…”
Section: Discussionmentioning
confidence: 99%
“…4-OD is a metal-dependent enzyme requiring magnesium ion for activity. Johnson and colleagues identified conserved and potential catalytic residues in XylI and homologues, and constructed XylI mutants that were expressed and purified as a complex with XylJ (VPH) . Two mutants (E109Q and E111Q) lacked the decarboxylase activity of 4-OD, but retained the hydratase activity of VPH.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to address these questions in the 4-OD/VPH complex from P. putida mt-2 have been limited by the fact that XylI is unstable in the absence of XylJ (6, 12, 13) . By using NahK from P. putida G7, we have now produced a stable 4-OD in large quantities that has similar kinetic parameters to those of 4-OD in the XylI/XylJ native complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 There are also some examples of HWE reactions of aromatic or short-chain aliphatic aldehydes with 2-fluorophosphonoacetates. Depending on the reaction conditions, 2-fluoro-or 2,4-difluorodienes were provided in good 2E- [19][20][21] or 2Z-selectivity. 20,22 HWE reactions, leading to analogues of retinoic acid bearing one vinylic fluorine atom in the 2-and/or 4-position on the polyene side chain, have also been described.…”
mentioning
confidence: 99%